ANALISIS PENDEKATAN SAINTIFIK PADA BUKU TEMATIK SISWA KELAS 3 SD/MI TEMA 6 REVISI 2018 - Raysa Abellia Nur Sukmaya; Ika Ratih Sulistiani; Mutiara Sari Dewi (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
2013 curriculum is used to prepare the golden generation and is implemented in order to improve the quality of national education through improving the quality of graduates by equipping students to think creatively, critically, with strong character, and able to take advantage of advances in information and technology in their development. Government efforts in developing the 2013 curriculum and changing the learning approach to be scientific. This research approach used is a qualitative approach to the type of discourse analysis, especially content analysis. The data in this study consisted of primary data in the form of thematic textbooks for class III theme 6 revision 2018 publishers of curriculum and bookkeeping centers, Balitbang, Kemendikbud. Meanwhile, secondary data, namely data sources that can support this research include books, journals, articles, government documents, websites, magazines, and other sources. Data analysis was performed by analyzing data from documentation techniques with the main source of thematic books for class III students in theme 6 of the 2018 revision, which began by reviewing thematic books and describing them in a description related to the suitability of class III thematic books for theme 6 revised 2018 with a scientific approach to primary schools. The results of this study are the subtitles and various kinds of material activities that have been presented in the book, this thematic book has fulfilled 5 components of a good textbook including learning instructions, supporting information, exercises, work instructions or worksheets, and finally evaluation but 1 component in this book is not displayed, i.e., the competencies to be achieved in each lesson are not written in the book. Keywords: 2013 Curriculum, Scientific Approach, Thematic Theme 6 Grade 3